Work redesign: Intervention based on the Social Information Processing Approach - Isabela Cortopassi Buso; Amalia Raquel Pérez-Nebra; Núria Tordera; Marina Kohlsdorf (Revista Psicologia)
The objective of this study was to measure the impact of a work redesign intervention based on the social information processing approach in an emotional work context. The research used a quasi-experimental panel design with pretest and post-test measurement, with intervention and control groups. A hundred and one health professionals participated in the study. Data were collected in 15-month intervals and 12 months after the intervention. We analyzed intergroup, intragroup, and psychological networks differences. Intergroup and intragroup analyses showed differences in the Information Processing category. The psychological network analysis suggested it was a protective, promising, and low-cost intervention for work redesign. The use of dynamic psychological network measures for intervention studies was discussed.